2013
DOI: 10.1037/a0031367
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of a body image exposure session on smoking urge between physically active and sedentary female smokers.

Abstract: Smoking is often used as a maladaptive weight control strategy among female smokers. Many of the perceived benefits accrued from smoking, including enhanced mood, reduced anxiety, and weight control, can also be achieved through physical activity. The purpose of this study was to examine the effects of a novel behavioral task (body-image exposure) that was designed to elicit body image and weight concerns on urge to smoke among 18-24 year old female smokers who vary in levels of physical activity. Using a cue-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…At the same time, sedentary behavior is significantly associated with mental illness, and prolonged sitting increases the risk of anxiety, depression, and suicide [ 37 ]. While another study has shown that for smokers, smoking can bring many perceived benefits, including enhanced mood, reduced anxiety, and weight control [ 38 ]. The negative effects of sedentary behavior may induce some people to smoke for relief.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, sedentary behavior is significantly associated with mental illness, and prolonged sitting increases the risk of anxiety, depression, and suicide [ 37 ]. While another study has shown that for smokers, smoking can bring many perceived benefits, including enhanced mood, reduced anxiety, and weight control [ 38 ]. The negative effects of sedentary behavior may induce some people to smoke for relief.…”
Section: Discussionmentioning
confidence: 99%
“…Such motives are common in adolescence. Scientists [33,34] argue that the motivational factors that provoke girls to smoke are social needs, namely: the desire to be "friendly" in the team, to hit the taste of the opposite sex, to establish communication processes (interaction) with peers, friends. These factors dominate in the adolescent and youth environment.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, physically active smokers may develop positive expectancies about the utility of exercise in aiding quit attempts, resulting in greater smoking cessation self-efficacy and lower need to further increase exercise during quit attempts. 46 However, because the present study was not designed to assess how exercise differentially affects physically active and sedentary smokers following smoking cessation, future work in this area is needed.…”
Section: Discussionmentioning
confidence: 99%